101RADIAL ARTERY VERSUS RIGHT INTERNAL THORACIC ARTERY AS THE BEST SECOND CONDUIT IN MULTI-ARTERIAL CORONARY ARTERY BYPASS GRAFTING: A MULTI-INSTITUTIONAL STUDY. (October 2014) - Schwann, T.A.; Hashim, S.W.; Bonnell, M.R.; Badour, S.; Obeid, M.; Tranbaugh, R.; Engoren, M.C.; Habib, R.H.
Abstract : Objectives: Multiple arterial coronary artery grafting (MABG) improves long-term survival compared to single arterial CABG (SABG), yet the best second arterial conduit remains undefined. Outcomes in patients grafted with radial artery (RA) versus right internal thoracic artery (BITA) as the second arterial graft were compared to SABG. Methods: Multi-institutional, retrospective analysis of non-emergent isolated left internal thoracic artery (LITA) to left anterior descending (LAD) CABG patients was performed using STS Cardiac Databases. A total of 4329 (54.4%) SABG (LITA ± SVG), 3006 (37.8%) RA (RA ± SVG) and 627 (7.9%) BITA (BITA ± SVG) patients were included. Long-term survival was ascertained from US Social Security Death Index. Triplet propensity matching was used to adjust for baseline differences between study cohorts. Results: Compared to the saphenous vein graft (SVG) cohort, the BITA cohort was younger (58.6 ± 10.2 vs 65.9 ± 10.4, P < 0.001), had a higher prevalence of males (87% vs 65%, P < 0.001) and was generally healthier (myocardial infarction: 36.7% vs 56.7%, smoking: 56.8% vs 61.1%, insulin-dependent diabetes mellitus: 3.0% vs 14.4%, cerebrovascular accident: 2.6% vs 10.0%, P < 0.001 for all). The RA cohort was generally characterised by a risk profile intermediate to that of SABG and BITA. The unadjusted 16-year survival rates were best in the BITA (84.6%), followed by the RA (75.6%) and worst in the SABG (55%) cohorts. Propensity matching yielded 551 well-matched RA, BITA and SVG triplets. Thirty-day mortality was equivalent; 16-year survival was equivalent in the RA and BITA cohorts (68.2% vs 66.7%, P = 0.127) and significantly better than in the SABG cohort (61.1%, BITA versus SVG, P < 0.002, RA versus SVG, P = 0.038), see Fig. 1. Conclusion: RA- or RITA-based MABG equally improves long-term survival compared to SABG and thus should be embraced by the heart team as optimal CABG strategy.